Variation in Coding Practices for Vestibular Schwannoma Surgery - Bi, Wenya Linda; Mooney, Michael A.; Yoon, Seungwon; Gupta, Saksham; Lawton, Michael T.; Almefty, Kaith K.; Corrales, C. Eduardo; Dunn, Ian F. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Nationwide databases are frequently used resources for assessing practice patterns and clinical outcomes. However, analyses based on billing codes may be limited by the inconsistent application of current procedural terminology (CPT) codes to specific operations. We investigated the variability among commonly used CPT codes for vestibular schwannomas resection and sought to identify factors that underlie this variation.Methods The surgical procedure for 274 cases of vestibular schwannoma resections from two institutions was reviewed and classified as retrosigmoid, translabyrinthine, or middle fossa approaches. We then assessed the CPT codes assigned to each case and analyzed their association with surgical approach, surgeons involved, the coding specialty, and year of surgery. We further compared the incidence of CPT codes assigned for vestibular schwannoma surgeries in the American College Surgeons National Surgical Quality Improvement Program (NSQIP) database from 2010 to 2014.Results The majority (65%) of vestibular schwannoma resections within the institutional cohort were billed with skull base approach and/or excision codes, whereas 76% of cases in NSQIP were associated with a single craniotomy for tumor code. The use of skull base codes over the past decade increased within our institutional cohort but remained relatively stable within NSQIP. CPT codes did not consistently reflect the operative approaches for vestibular schwannomas.Conclusion We observed significant variability in coding patterns for vestibular schwannoma surgeries within institutions, surgical practices, and national databases. These results call for discretion in interpretation of data from aggregated billing code-based nationwide databases and suggests a role for institutional standardization of CPT assignments for the same approaches.
Keywords: vestibular schwannoma; acoustic neuroma; skull base surgery; CPT coding; practice patterns